Comparison of Super-Profit State Business Entities Law Based on Justice Values - Slamet Edy Purnomo; Serhii Vitvitskyi; Viacheslav Davydenko; Dian Pramana (Unissula, 2026)
State-Owned Enterprises in Indonesia bear a dual burden as development agents that prioritize public service and, at the same time, as business entities required to generate substantial profits. A paradox arises when SOEs record massive profits, while society continues to experience economic injustice caused by tariffs, interest rates, or monopolistic prices that create public burdens. This article aims to reconstruct SOE regulations based on justice values so that the orientation toward super-profit does not undermine public welfare. This study employs a doctrinal legal research method using statutory, conceptual, and comparative legal approaches to state business systems in Singapore, Norway, and China. The study finds that a clear separation or a profit-distribution formula is needed so that SOE profits can be transparently returned to the public through public subsidies. The reconstruction of SOE regulations should be directed toward separating commercial SOEs from public-service SOEs, regulating profit-margin limits in essential sectors, and allocating a portion of super-profit SOE dividends to public welfare programs. Such reform positions SOEs as financially sound business entities while also serving as instruments of distributive justice in accordance with the mandate of Constitution.